Subacute cutaneous lupus erythematosus on the lines of Blaschko - Röckmann, Heike; Schadendorf, Dirk; Goerdt, Sergij (European journal of dermatology, 2006)
We describe a 42-year-old woman who had erythemateous plaques with sharply demarcated margins and fine scaling on her right trunk and leg. The lesions had a linear distribution following the lines of Blaschko. Histological findings supported the diagnosis of subacute cutaneous lupus erythematosus (SCLE) on the lines of Blaschko. Treatment with systemic corticosteroids and anti-malarial agents resulted in remission. Up to now, eighteen cases of linear lupus erythematosus have been described. Linear lupus erythematosus mostly affects children presenting with lesions on the scalp that were classified as discoid lupus erythematosus. To our knowledge, this is the first case of subacute cutaneous lupus erythematosus on the lines of Blaschko.
Gesehen am 10.02.2021